An empirical study on optic disc segmentation using an active contour model. (April 2015) - Mary, M. Caroline Viola Stella; Rajsingh, Elijah Blessing; Jacob, J. Kishore Kumar; Anandhi, D.; Amato, Umberto; Selvan, S. Easter
Abstract : Graphical abstract: Abstract : Highlights: Active contour models (ACMs) detecting optic disc (OD) boundaries are investigated. Images are subject to adaptive histogram equalization and morphological operations. Various ACMs are initialized with contours estimated by circular Hough transform. Gradient-vector-flow-based ACM outclasses the rest with a statistical significance. Segmented ODs are accurate, and the approach incurs less computational burden. Abstract: The accurate segmentation of the optic disc (OD) offers an important cue to extract other retinal features in an automated diagnostic system, which in turn will assist ophthalmologists to track many retinopathy conditions such as glaucoma . Research contributions regarding the OD segmentation is on the rise, since the design of a robust automated system would help prevent blindness, for instance, by diagnosing glaucoma at an early stage and a condition known as ocular hypertension . Among the evaluated OD segmentation schemes, the active contour models (ACMs) have often been preferred by researchers, because ACMs are endowed with several attractive properties. To this end, we designed an OD segmentation scheme to infer how the performance of the well-known gradient vector flow (GVF) model compares with nine popular/recent ACM algorithms by supplying them with the initial OD contour derived from the circular Hough transform . The findings would hopefully equip a diagnostic system designer with an empirical support to ratify the choice of a specific model as we are bereft of such a comparative study. A dataset comprising 169 diverse retinal images was tested, and the segmentation results were assessed by a gold standard derived from the annotations of five domain experts. The segmented ODs from the GVF-based ACM coincide to a greater degree with those of the experts in 94% of the cases as predicted by the least overall Hausdorff distance value (33.49 ± 18.21). Additionally, the decrease in the segmentation error due to the suggested ACM has been confirmed to be statistically significant in view of the p values (≤1.49e−09) from the Wilcoxon signed-rank test . The mean computational time taken by the investigated approaches has also been reported.